COVID-19 and treatment with NSAIDs and corticosteroids: should we be limiting their use in the clinical setting? - Russell, Beth; Moss, Charlotte; Rigg, Anne; Van Hemelrijck, Mieke (Ecancermedicalscience, 2020)
Given the current SARS-CoV-2 (COVID-19) pandemic, the availability of reliable information for clinicians and patients is paramount. There have been a number of reports stating that non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids may exacerbate symptoms in COVID-19 patients. Therefore, this review aimed to collate information available in published articles to identify any evidence behind these claims with the aim of advising clinicians on how best to treat patients. This review found no published evidence for or against the use of NSAIDs in COVID-19 patients. Meanwhile, there appeared to be some evidence that corticosteroids may be beneficial if utilised in the early acute phase of infection, however, conflicting evidence from the World Health Organisation surrounding corticosteroid use in certain viral infections means this evidence is not conclusive. Given the current availability of literature, caution should be exercised until further evidence emerges surrounding the use of NSAIDs and corticosteroids in COVID-19 patients.